Preconcentration and Determination of Cadmium in Natural Water using Amberlite XAD-4/4-(2- Pyridylazo) Resorcinol Resin Prior to Flame Atomic Absorption Spectrometric Detection - Sanguthai, Sureerat; Klamtet, Jintana (Naresuan University Journal: Science and Technology (NUJST); Vol 23 No 2 (2015): May-August 2015, 2015)
A chelating polymeric sorbent was developed by functionalizing Amberlite XAD-4 resin with 4-(2-pyridylazo) resorcinol ligand for preconcentration of Cd(II) and quantitative analysis by flame atomic absorption spectrometry. The effect of several parameters such as pH, adsorption time, adsorption capacity, preconcentration factor, effect of interference and concentration of nitric acid were studied in a batch system. Optimized conditions with a pH of value 9.0, loading time of 30 min and nitric concentration of 0.5 mol l-1 were selected. The detection limit of the method was found to be 0.26 mg l-1. The chelating resin can be reused for sorption–desorption and is stable for up to 15 runs (recovery 85-91%) without appreciable loss of sorption capacity. The preconcentration factor achieved by this method is 5. The effects of interferences are reported. The precision of the method was evaluated with the relative standard deviations (R.S.D.) under optimum conditions being 1.78 and 0.29% (n=10) for 0.40 and 1.20 mg l-1of Cd(II), respectively. The proposed method has been applied for the determination of Cd (II) ions in water samples collected around Naresuan University, Phitsanulok Province. Keywords: XAD-4 resin, Amberlite XAD-4/PAR resin, Solid phase extraction, Preconcnetration, Cadmium
Keywords: XAD-4 resin, Amberlite XAD-4/PAR resin, Solid phase extraction, Preconcnetration, Cadmium